Non-invasive haemodynamic monitoring with Clearsight in patients undergoing spinal anaesthesia for total hip replacement. A prospective observational cohort study.: Clearsight monitoring for spinal block - Ghisi, Daniela; Garroni, Marco; Giannone, Sandra; De Grandis, Giovanni; Fanelli, Andrea; Sorella, Maria Cristina; Bonarelli, Stefano; Melotti, Rita Maria (Acta Biomedica Atenei Parmensis, 2020)
Background: Patients undergoing elective primary total hip replacement and spinal anesthesia may encounter significant hemodynamic instabilityObjective: The study is aimed at observing the haemodynamic modifications after spinal anaesthesia during total hip replacement in patients managed to "preload independence" with goal directed fluid therapy (GDFT) and monitored non-invasively with Clearsight.Methods: Thirty patients, aged 50-80 years, with an American Society of Anaesthesiologists' (ASA) score II-III, undergoing elective primary total hip replacement and spinal anaesthesia were enrolled. Patients were monitored with the EV1000 platform and the Clearsight finger-cuff and managed with a goal directed fluid therapy.Results: The 79% of the population showed preload independence at baseline. After spinal, the 93% did not show a significant mean arterial pressure reduction. In our population, 79% reported a decrease >10% of the stroke volume during surgery, while 66% in the Recovery Room. Patients showed an improvement in mean arterial pressure, systemic vascular resistances indexed (SVRI), stroke volume (SV) and stroke volume indexed (SVI) at spinal resolution compared to baseline.Conclusions: Our cohort population showed hemodynamic stability throughout the study period, with increased SV and decreased SVRI at spinal resolution compared to basal values. Further randomized prospective studies are advocated in the same setting.